Perbandingan Kelayakan Usaha dan Sensitifitas Harga Telur asin Original dan Daun Jintan Plectanthrus amboinicus) Tanpa Bau Amis Rasa Pedas Cabe Merah - Sundari, Ristina Siti; Yuninda, Resti; Hidayati, Reny; Fitriadi, Budhi Wahyu (Universitas Galuh, 2025)
The potential for diversification of processed salted egg products that have high economic value is still wide open. To increase the competitiveness and added value of the product, innovation is needed through the addition of natural ingredients to make it richer in taste and not smell fishy. Therefore, this study aims to analyze the comparative feasibility of the original salted egg business with the variant of adding oregano leaves with a spicy red chili flavor. The research method used is descriptive quantitative regarding the analysis of the feasibility of the business calculation of fixed costs, variable costs, revenue, income, R/C ratio, and elasticity. Data collection was carried out through experiments in the Agribusiness laboratory, Faculty of Agriculture, University of Perjuangan Tasikmalaya. The results of this study indicate that the formulation of salted eggs with the addition of oregano leaves (Plectranthus amboinicus) and red chili has a positive impact on sensory, economic, and strategic aspects. Sensorially, there was a significant increase in the attributes of herbal aroma, spicy taste, and aftertaste, and a decrease in fishy odor, which is thought to be influenced by the volatile aromatic compounds from oregano leaves. Economically, this treatment generates a net income of Rp792,777; the R/C ratio of 2.70 indicates that this innovation is very efficient and worth developing. Sensitivity analysis of selling price (Rp6,500–Rp7,500) and production volume (180–300 grains) indicates that both premium pricing strategies and production expansion have a positive impact on profitability. This innovative product has comparative and differentiating advantages in positioning itself as a gourmet product or functional red chili pepper oregano leaves